Influence Recovery on Pattern Sleep Towards Female Basketball Athletes of MA Central Jakarta - Setiawan, Muhammad Arief; Aulia, Danny; Sentana, Bima; Saputra S, Misbahudin Nanda Agung; Putri, Ananda Mulia; Alkautsar, Fata Azima; Nabilahasha, Anggi (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This research explores the impact of recovery on sleep patterns among female basketball athletes from MA Central Jakarta. Adequate sleep is essential for optimal physical and psychological performance, particularly in sports. Poor sleep patterns can lead to fatigue, decreased immune function, and suboptimal athletic performance. This study aims to assess the knowledge and habits of these athletes regarding sleep recovery and its implications for their performance. A descriptive statistical approach was utilized, involving a purposive sampling of 10 athletes aged 16-19 years. Data were collected using an online questionnaire with 18 structured questions focusing on sleep recovery patterns. The analysis employed the Guttman scale with binary responses ("Yes" or "No"). Findings revealed that 70% of the responses indicated poor sleep patterns, including inconsistent sleep schedules and frequent use of technology before bedtime. These habits negatively influenced their recovery, contributing to fatigue and reduced performance during training and competition. The study underscores the importance of sufficient sleep, ideally 8-10 hours per night, for maintaining physical fitness and enhancing athletic performance. The research concludes that interventions are needed to improve sleep habits among these athletes. Recommendations include establishing consistent sleep routines and educating athletes on the significance of sleep for recovery. Future studies should explore broader populations and evaluate interventions for promoting better sleep practices among athletes.